Conformational modulation of peptides using β-amino benzenesulfonic acid (SAnt). Issue 7 (18th December 2014) - Priya, Gowri; Kotmale, Amol S.; Chakravarty, Debamitra; Puranik, Vedavati G.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J.
Abstract : This communication describes the utility of the conformationally restricted aromatic β-amino acid (2-aminobenzenesulfonic acid, S Ant) for inducing various folding interactions in short peptides. Abstract : This communication describes the utility of a conformationally restricted aromatic β-amino acid (2-aminobenzenesulfonic acid, S Ant) inducing various folding interactions in short peptides. Sandwiching S Ant between diverse amino acid residues was shown to form robust folded architectures featuring a variety of H-bonded networks, suggesting its utility in inducing peptide folding.